Minimal Brain Dysfunction (MBD) and its Impact on Musculoskeletal Deformities: Causes, Symptoms and Physiotherapy Interventions - Tomasz Karski; Jacek Karski; Klaudia Karska; Paul Ochen (Disease and Health: Research Developments Vol. 5, 2025)
Some children’s “muscular-skeletal system” disorders can be seen early in newborns and babies. They are symptoms of Minimal Brain Dysfunction (MBD). These abnormalities are caused by an asphyxia of the fetus during pregnancy or delivery. This study discusses Minimal Brain Dysfunction (MBD) and Its Impact on Musculoskeletal Deformities. This study also discusses the causes, symptoms, and physiotherapy interventions of MBD. Among various disorders of the locomotor system in children and also in youth patients, there are changes connected with the functioning of the Central Nervous System. Children with MBD have also psychological changes in their behavior. In the diagnosis, it is important to inquire about the gravidity and the delivery. Early therapy is the best prophylaxis of pain syndromes and arthrosis of the feet, knees, hips, and spine in adults.